2015
DOI: 10.1038/nnano.2015.165
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous ultrafast dynamics of hot plasmonic electrons in nanostructures with hot spots

Abstract: The interaction of light and matter in metallic nanosystems is mediated by the collective oscillation of surface electrons, called plasmons. After excitation, plasmons are absorbed by the metal electrons through inter- and intraband transitions, creating a highly non-thermal distribution of electrons. The electron population then decays through electron-electron interactions, creating a hot electron distribution within a few hundred femtoseconds, followed by a further relaxation via electron-phonon scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
303
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(319 citation statements)
references
References 30 publications
(33 reference statements)
9
303
0
Order By: Relevance
“…Ultrafast pump-probe measurements of plasmonic nanostructures use a high-intensity laser pulse to excite a large number of electrons and measure the optical response as a function of time using a delayed probe pulse [77,78]. The typical signal observed in these experiments is an initial fast rise (10-100 fs) attributed to electron-electron scattering that converts fewer high-energy excited carriers into several more lower-energy carriers, followed by a slower decay (100 fs to 1 ps) attributed to electron-phonon scattering.…”
Section: Hot Carrier Dynamics: Ultrafast and Fast Timescalesmentioning
confidence: 99%
“…Ultrafast pump-probe measurements of plasmonic nanostructures use a high-intensity laser pulse to excite a large number of electrons and measure the optical response as a function of time using a delayed probe pulse [77,78]. The typical signal observed in these experiments is an initial fast rise (10-100 fs) attributed to electron-electron scattering that converts fewer high-energy excited carriers into several more lower-energy carriers, followed by a slower decay (100 fs to 1 ps) attributed to electron-phonon scattering.…”
Section: Hot Carrier Dynamics: Ultrafast and Fast Timescalesmentioning
confidence: 99%
“…First, Harutyunyan et al 47 reported anomalous ultrafast dynamics of plasmonic hot electrons in hybrid metal/oxide NSs with hot spots when they varied the geometry and composition of the NS and the excitation wavelength. They showed a large ultrafast contribution to the excited electron decay signal in the hybrid NSs of gold nanodisks with diameters of 100-150 nm on top of a 30-nm-thick continuous gold film separated by a spacer layer (several nanometers thick) containing hot spots.…”
Section: Mechanism Revealed By Ultrafast Spectroscopymentioning
confidence: 99%
“…The TCO-based structures have been demonstrated to produce responsivity up to 70 mA/W under a reverse bias of −3 V in the visible regime [112] (Figure 3F). In terms of detection speed, recent ultrafast studies on hot electron relaxation dynamics [117] have revealed hot electron relaxation times as fast as ~45 fs. Furthermore, the speed was strongly dependent on the local field enhancement and therefore can be controlled by tailoring the plasmonic geometry.…”
Section: Free-space Photodetectorsmentioning
confidence: 99%
“…For hot carrier distribution, although much work has been devoted to providing theoretical predictions of hot carrier distribution in plasmonic nanostructures [30,31,69,71,72,158], more experimental work is needed to validate these models. In addition, a better understanding of the hot carrier relaxation timescale [75,117,[159][160][161] in various materials as well as the transport dynamics in nanostructures would provide more valuable information for designing plasmonic devices with efficient hot carrier transport to the Schottky interface. Lastly, engineering the metal-semiconductor interface on the atomic level could also lead to improved hot electron transfer efficiencies [157,162].…”
Section: -156mentioning
confidence: 99%